2017
DOI: 10.1021/acs.bioconjchem.7b00583
|View full text |Cite
|
Sign up to set email alerts
|

Last-Step Pd-Mediated [11C]CO Labeling of a Moxestrol-Conjugated o-Iodobenzyl Alcohol: From Model Experiments to in Vivo Positron Emission Tomography Studies

Abstract: The fast, efficient, and functional group tolerant last-step radiolabeling of bioconjugates is crucial for positron emission tomography (PET) applications. In this context, o-iodobenzyl alcohol based structures were identified as ideal tags for an easy Pd-catalyzed carbonylation after bioconjugation, and a moxestrol-conjugated precursor was chosen as the model compound for the further studies. Despite scale and time constraints, conditions developed with [C]CO and [C]CO were easily transferred to the C isotope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…Two molecules of biological interest were labeled in this study: (i) moxestrol, a steroid ligand with a specificity for the estrogen receptor (ER); and (ii) cyclo-RGD, a cyclopeptide targeting the integrin αvβ3 receptors, which are implicated in different forms of cancer. In a follow-up study, the same group reported the initial evaluation of the [ 11 C]moxestrol conjugate as a potential PET radioligand for the in vivo visualization of ERs [ 57 ]. Unfortunately, no specific binding was detected in vivo using PET−MRI imaging.…”
Section: Pd–xantphos-based Radiochemistry For the Synthesis Of Bioact...mentioning
confidence: 99%
“…Two molecules of biological interest were labeled in this study: (i) moxestrol, a steroid ligand with a specificity for the estrogen receptor (ER); and (ii) cyclo-RGD, a cyclopeptide targeting the integrin αvβ3 receptors, which are implicated in different forms of cancer. In a follow-up study, the same group reported the initial evaluation of the [ 11 C]moxestrol conjugate as a potential PET radioligand for the in vivo visualization of ERs [ 57 ]. Unfortunately, no specific binding was detected in vivo using PET−MRI imaging.…”
Section: Pd–xantphos-based Radiochemistry For the Synthesis Of Bioact...mentioning
confidence: 99%
“…作者实现了糖类、生物素、核苷和环 状蛋白等多种生物分子的偶联, 并用化学计量的 13 C 进 行了良好的标记(Scheme 13). 年, 该课题组 [36] 利用 同样的策略合成了 13 CO 标记的莫克雌醇衍生物, 该化 合物在雌鼠体内具有极好的稳定性. 2019 年, Hermange 课题组 [37] 以三苯基膦为配体, 使 图式 13 硅基羧酸释放 CO 用于示踪剂的合成 Scheme 13 Tracer synthesis with CO released from silicic acid 13 C 标记的硅基羧酸作为 13 CO 源, 将该络合物与 13 CO 用于制备各种内酯化合物(75) (Scheme 14).…”
Section: 硅基羧酸作为 Co 前体参与的反应unclassified